Pengaruh Motivasi Guru Terhadap Prestasi Belajar Siswa dalam Rangka Meningkatkan Tumbuhnya Aktivitas Belajar Siswa dan Fungsi Guru Sebagai Motivator - Lisda Rahmayanti (Integrated Education Journal, 2024)
Education is a process that is intertwined with both personal existence and society. In order to increase motivation and grow student learning activities, the teacher's function as a motivator is very important. The aim of this research is to find out how well teachers use motivation and to find out how much influence teacher motivation has on student learning achievement. In improving learning achievement, teachers must be able to develop motivation in every teaching and learning activity. For this reason, it is necessary to have a communicative teaching and learning atmosphere between teachers and students, because it can arouse students' learning motivation to carry out learning activities effectively and efficiently. This research uses a qualitative approach, namely describing and explaining the influence of teacher motivation on student learning achievement. The data collection technique used in this research is library study where library study is the activity of collecting materials related to research originating from books, scientific journals, literature and other publications that are suitable as sources for future research. researched by the author, by describing and explaining the data through several expert opinions. The results of this research show that good teacher motivation can significantly increase student learning achievement.